Computational Model for Internal Relative Humidity Distributions in Concrete. (9th March 2014) - Ali, Wondwosen; Urgessa, Girum
Abstract : A computational model is developed for predicting nonuniform internal relative humidity distribution in concrete. Internal relative humidity distribution is known to have a direct effect on the nonuniform drying shrinkage strains. These nonuniform drying shrinkage strains result in the buildup of internal stresses, which may lead to cracking of concrete. This may be particularly true at early ages of concrete since the concrete is relatively weak while the difference in internal relative humidity is probably high. The results obtained from this model can be used by structural and construction engineers to predict critical drying shrinkage stresses induced due to differential internal humidity distribution. The model uses finite elment-finite difference numerical methods. The finite element is used to space discretization while the finite difference is used to obtain transient solutions of the model. The numerical formulations are then programmed in Matlab. The numerical results were compared with experimental results found in the literature and demonstrated very good agreement.